Hemostatic disorders of the menopausal period: the role of microRNA - Stachowiak, Grzegorz; Zając, Agnieszka; Nowak, Marek; Stetkiewicz, Tomasz; R. Wilczyński, Jacek (Menopause Review/Przegląd Menopauzalny, 2015)
Adverse changes in hemostasis of menopausal women, observed e.g. in atherosclerotic or neoplastic cases, are of multicausal origin. It is believed that in the development and regulation of these processes, an important role is played by microRNA particles, which presence is ascertained in endothelial cells, atherosclerotic plaques and systemic circulation. Discovered for the first time over 20 years ago, up to now over two and a half thousand types of microRNA have been identified in the human body. MicroRNAs are single stranded RNA molecules of 20-24 nucleotides, encoded by the cell’s genome and then transcribed by polymerase II. They regulate the expression of a large gene pool, approximately 30% of all genes, in the human body. MicroRNA molecules, like other bioactive molecules – RNA, protein – both play important roles in tumor invasion, metastasis, inflammation, coagulation, and regeneration. What is important, they can be detected not only in tissues (e.g. tumor tissues), but also in circulation (blood serum), where they are released. Accurate understanding of the role played by certain types of microRNA (e.g. miR-126, miR-17-92, miR-33, miR-613, miR-27a/b, miR-143, miR-335, miR-370, miR-122, miR-19b, miR-520, or miR-220) in hemostatic processes may allow in the future for their use not only as specific biomarkers of cardiovascular diseases but also as the target for innovative gene therapies.